IMPROVEMENT OF EDIBLE BIOPOLYMER FILM PRODUCTION TECHNOLOGY AND INVESTIGATION OF ITS BIODEGRADATION PROCESS - S.N.Obloberdiyev; G.Sh.Korabekova; F.Sh.G‘ulomova; M.J.Bekmurodova; Sh.E.Ulashova; Z.A.Madusmonova (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation. This study focuses on improving the production technology of edible biopolymer films and investigating their biodegradation process. The research evaluates the formation of a thin, flexible and environmentally safe film suitable for food packaging applications. Special attention is given to technological parameters, film-forming properties, physical appearance, usability, and natural degradation under environmental conditions. The obtained results may contribute to the development of eco-friendly, biodegradable and safe packaging materials as an alternative to synthetic plastic films.